Состояние подроста в спелых и приспевающих насаждениях Пермского края - Малеев, Кирилл Иванович; Жебряков, Вениамин Николаевич; Чикунов, Михаил Леонидович (Географический вестник=Geographical bulletin, 2017)
нет аннотации